Drug-drug interactions between antithrombotics and direct-acting antivirals in hepatitis C virus (HCV) patients: A brief, updated report - Canonico, Mario Enrico; Sanna, Giuseppe Damiano; Siciliano, Roberta; Scudiero, Fernando; Esposito, Giovanni; Parodi, Guido (Frontiers in Pharmacology, 2022)
Hepatitis C virus (HCV) is one of the leading causes of chronic liver disease affecting over 71 million people worldwide. An increased incidence of atherothrombotic events [e.g. coronary artery disease (CAD), atrial fibrillation (AF)] has been observed in HCV seropositive patients. On the other hand, an increased bleeding risk is another clinical issue, particularly in subjects with liver cirrhosis, gastroesophageal varices, portal hypertension, thrombocytopenia and alcohol consumption. The introduction and progressively greater use of direct-acting antivirals (DAAs) (instead of protease and polymerase inhibitors) during the last decade has enabled a sustained virological response to be achieved in a significant percentage of patients. However, due to the high cardiovascular risk profile in HCV-infected patients, the concomitant use of antithrombotic therapies is often required, bearing in mind the possible contraindications. For example, despite better pharmacokinetic and pharmacodynamic properties compared with vitamin K-antagonists, plasma level fluctuations of direct oral anticoagulants (DOACs) due to pathological conditions (e.g. chronic kidney diseases or hepatic cirrhosis) or drug-drug interactions (DDIs) may be of great importance as regards their safety profile and overall clinical benefit. We aimed to examine and briefly summarize the significant DDIs observed between antithrombotic and HCV antiviral drugs.